The context marketing revolution : how to motivate buyers in the age of infinite media - Sweezey, Mathew (Boston, MA : Harvard Business Review Press, 2019)
"In a world of limitless media noise, how can businesses break through to customers? Context. We are in the midst of a massive media revolution. For the first time in history, ordinary people around the world have the ability to create, distribute, and consume content instantly, from anywhere, using connected devices. The massive increase in media "noise" created by these consumers and devices creates an entirely new situation that conventional marketing models are not set up for and can't handle. And yet countless companies and marketing organizations continue to rely on traditional models, assuming that their "campaigns" will sway customers. They couldn't be more wrong. In this provocative and practical book, Salesforce marketing maven Mathew Sweezey boldly outlines this new "infinite media" environment and poses a profound question: In a transformed world where customers shape their own experience, what is the key to breaking through and motivating them to buy? It is context--the close linkage between an individual's immediate desires and the experiences a brand creates to fulfill them. Drawing on new research and new insights into current consumer psychology, Sweezey defines the five key elements of context. Customer experiences must be: Available: Helping people achieve the value they seek in the moment Permissioned: Giving people what they've asked for, on their terms Personal: Going beyond how personal it is to how personally you can deliver it Authentic: Combining voice, empathy, and brand congruence simultaneously Purposeful: Creating a deeper connection to the brand, beyond the product Sweezey uses vivid examples and cases to highlight a new marketing model used by high-performing brands big and small. The final part of the book shifts to execution, providing a new rule book for context-based marketing. The Context Marketing Revolution will change forever how you think about the purpose and practice of marketing and what it means to be a modern brand"--
Introduction: Why context is king -- Part one. How infinite media has transformed your business forever: Three keys to the context marketing revolution -- New consumer -- new consumer journey -- Part two. How context works in marketing: The context framework: breaking through the noise -- Available (helping people achieve the value they seek in the moment) -- Permissioned (coordinating with individuals to give them what they've asked for, on their terms) -- Personal (going beyond how personal the experience is to how personally you can deliver it) -- Authentic (combining voice, empathy, and channel congruence simultaneously) -- Purposeful (creating a deeper connection to the brand beyond the product) -- Part three. How to market brands in the infinite media era: Shifting from campaigns to customer journeys -- Triggers along the journey -- Using automation to guide journeys -- Faster, better: building agile processes into the journey -- A new business model for the context marketing revolution -- The first step, and final thoughts.
Includes index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Added to collection customer.56279.3
Keywords: Consumers' preferences; Context effects (Psychology); Market segmentation; Branding (Marketing); Branding (Marketing); Consumers' preferences; Context effects (Psychology); Market segmentation; elektronické knihy; electronic books